Effect of Eurycoma longifolia Jack Root Extract on Sperm pH and Morphology in Nicotine-Exposed Rats - Irenesia, Bimby; Afri Yati, Umaimah; Utami, Riski Dwi; Marwan, Deinike Wanita (Indonesian Journal of Pharmaceutical Education, 2025)
Infertility is the inability of couples of childbearing age (PUS) to conceive offspring. Male infertility can be caused by several trigger factors, one of which is smoking. One of the ingredients contained in cigarettes is nicotine which can cause free radicals. As a result of free radicals, there is damage to spermatozoa DNA. The sterol and isoprenoid content in pasak bumi can prevent infertility in men. both of these ingredients are necessary for the synthesis of steroid hormones. Steroid hormones play a critical role in spermatozoa development. The objective of this study to determine the effect of administering pasak bumi root extract on the pH and sperm morphology of male Wistar rats exposed to nicotine. This research is experimental with a posttest-only control design. The research was carried out for 51 days and the analysis used was the one way anova test. In the results of the spermatozoa pH examination, there was no influence in the treatment group or control group, whereas in the morphology examination there was an influence or difference at doses of 50, 100, and 200 100 mg/kgBW with (p-value 0.05). Pasak bumi root extract (Eurycoma longifolia Jack) on the morphology of spermatozoa in male Wistar rats exposed to nicotine. In research, the pH of pasak bumi root extract (Eurycoma longifolia Jack) had no effect on the pH of spermatozoa exposed to nicotine.